Proselitismo versus laicidade: as concepções da prática pedagógica de professoras do ensino religioso das escolas públicas do município de Jandira - Medeiros, Roberto da Silva (2025)
This dissertation aims to analyze the representations of Religious Education teachers, focusing on the tensions between proselytism and secularism. To this end, initially, the insertion of this curricular component in the Brazilian educational system was contextualized through the analysis of constitutional provisions and legal systems of education in Brazil from the beginning of the republican period to the present day. The field research was carried out with 28 teachers from three municipal Basic Education schools in the Municipality of Jandira who, although multipurpose, teach the subject of Religious Education in Elementary School I. The instrument used for data collection was a semi-open questionnaire that for better organization, was divided into three blocks of questions: a) Training trajectory of Religious Education teachers from the Jandira Municipal Network; b) Teachers’ perceptions about Religious Education in the Municipality of Jandira; C) Proselytism and secularism: Perceptions expressed by teaching practice. Among the findings resulting from the analysis of the responses, the following stand out: the interdependent relationships between the political, religious, and educational fields, revealing a religious habitus legitimized in the concrete tensions between religion and education / proselytism and secularism